Industrial organic chemicals - Wittcoff, Harold (Wiley, 2013)
"Providing 95 percent of the 500 billion pounds of organic chemicals produced in the world, the petroleum and natural gas industries are responsible for products that ensure our present quality of life. Products as diverse as gasoline, plastics, detergents, fibers, pesticides, tires, lipstick, shampoo, and sunscreens are based on seven raw materials derived from petroleum and natural gas. In an updated and expanded Third Edition, Industrial Organic Chemicals examines why each of these chemical building blocks-ethylene, propylene, C4 olefins (butenes and butadiene), benzene toluene, the xylenes, and methane-is preferred over another in the context of an environmental issue or manufacturing process, as well as their individual chemistry, derivatives, method of manufacture, uses, and economic significance."--